Design of a TiAlON multilayer coating: Oxidation stability and deformation behavior - Bobzin, K.; Kalscheuer, C.; Grundmeier, G.; de los Arcos de Pedro, Maria Teresa; Schwiderek, S.; Carlet, M. (Surface and Coatings Technology)

In situ backside Raman spectroscopy of zinc oxide nanorods in an atmospheric‐pressure dielectric barrier discharge plasma - Knust, Steffen; Ruhm, Lukas; Kuhlmann, Andreas; Meinderink, Dennis; Bürger, Julius; Lindner, Jörg K. N.; de los Arcos de Pedro, Maria Teresa; Grundmeier, Guido (Journal of Raman Spectroscopy)

Thermostable water reservoirs in the interlayer space of a sodium hectorite clay through the intercalation of γ-aminopropyl(dimethyl)ethoxysilane in toluene - Keil, Waldemar; Zhao, Kai; Oswald, Arthur; Bremser, Wolfgang; Schmidt, Claudia; Hintze-Bruening, Horst (Physical Chemistry Chemical Physics)
Thermostable compartmentalized sodium-water sites through intercalated γ-aminopropyl-dimethyl-ethoxy silane in synthetic hectorite.
Keywords: Physical and Theoretical Chemistry; General Physics and Astronomy

Review of infrared spectroscopy techniques for the determination of internal structure in thin SiO2 films - de los Arcos, Teresa; Müller, Hendrik; Wang, Fuzeng; Damerla, Varun Raj; Hoppe, Christian; Weinberger, Christian; Tiemann, Michael; Grundmeier, Guido (Vibrational Spectroscopy)
A comparison of infrared spectroscopic analytical approaches was made in order to assess their applicability for internal structure characterization of SiO2 thin films. Markers for porosity and/or disorder based on the analysis of the asymmetric stretching absorption band of SiO2 between 900−1350 cm−1 were discussed. The shape of this band, which shows a well-defined LO–TO splitting, depends not only on the inherent characteristics of the film under analysis but also on the particular geometry of the IR experiment and the specific surface selection rules of the substrate. Three types of SiO2 thin films with clearly defined porosity ranging from dense films to mesoporous films were investigated by transmission (at different incidence angles), direct specular reflection (at different angles), and diffuse reflection. Two different types of substrate, metallic and semiconducting, were used. The combined effect of substrate and specific technique in the final shape of the band, was discussed, and the efficacy for their applicability to the determination of porosity in thin SiO2 films was critically evaluated.

TiO2 nanoparticle coatings on glass surfaces for the selective trapping of leukemia cells from peripheral blood - Garcia Diosa, Jaime Andres; Gonzalez Orive, Alejandro; Weinberger, Christian; Schwiderek, Sabrina; Knust, Steffen; Tiemann, Michael; Grundmeier, Guido; Keller, Adrian; Camargo Amado, Ruben Jesus (Journal of Biomedical Materials Research Part B: Applied Biomaterials)
Photodynamic therapy (PDT) using TiO2 nanoparticles has become an important alternative treatment for different types of cancer due to their high photocatalytic activity and high absorption of UV-A light. To potentiate this treatment, we have coated commercial glass plates with TiO2 nanoparticles prepared by the sol–gel method (TiO2-m), which exhibit a remarkable selectivity for the irreversible trapping of cancer cells. The physicochemical properties of the deposited TiO2-m nanoparticle coatings have been characterized by a number of complementary surface-analytical techniques and their interaction with leukemia and healthy blood cells were investigated. Scanning electron and atomic force microscopy verify the formation of a compact layer of TiO2-m nanoparticles. The particles are predominantly in the anatase phase and have hydroxyl-terminated surfaces as revealed by Raman, X-ray photoelectron, and infrared spectroscopy, as well as X-ray diffraction. We find that lymphoblastic leukemia cells adhere to the TiO2-m coating and undergo amoeboid-like migration, whereas lymphocytic cells show distinctly weaker interactions with the coating. This evidences the potential of this nanomaterial coating to selectively trap cancer cells and renders it a promising candidate for the development of future prototypes of PDT devices for the treatment of leukemia and other types of cancers with non-adherent cells.

Zinc Anodizing: Structural Diversity of Anodic Zinc Oxide Controlled by the Type of Electrolyte - Engelkemeier, Katja; Sun, Aijia; Voswinkel, Dietrich; Grydin, Olexandr; Schaper, Mirko; Bremser, Wolfgang (ChemElectroChem)

Analytical characterization of polyamide 11 used in the context of selective laser sintering: Physico-chemical correlations - Scherer, Beate; Kottenstedde, Ingo Leonard; Bremser, Wolfgang; Matysik, Frank-Michael (Polymer Testing)

GIWAXS-SIIRkit: scattering intensity, indexing and refraction calculation toolkit for grazing-incidence wide-angle X-ray scattering of organic materials - Savikhin, Victoria; Steinrück, Hans-Georg; Liang, Ru-Ze; Collins, Brian A.; Oosterhout, Stefan D.; Beaujuge, Pierre M.; Toney, Michael F. (Journal of Applied Crystallography)
Grazing-incidence wide-angle X-ray scattering (GIWAXS) has become an increasingly popular technique for quantitative structural characterization and comparison of thin films. For this purpose, accurate intensity normalization and peak position determination are crucial. At present, few tools exist to estimate the uncertainties of these measurements. Here, a simulation package is introduced called GIWAXS-SIIRkit , where SIIR stands for scattering intensity, indexing and refraction. The package contains several tools that are freely available for download and can be executed in MATLAB. The package includes three functionalities: estimation of the relative scattering intensity and the corresponding uncertainty based on experimental setup and sample dimensions; extraction and indexing of peak positions to approximate the crystal structure of organic materials starting from calibrated GIWAXS patterns; and analysis of the effects of refraction on peak positions. Each tool is based on a graphical user interface and designed to have a short learning curve. A user guide is provided with detailed usage instruction, tips for adding functionality and customization, and exemplary files.

Crystallization and Organic Field‐Effect Transistor Performance of a Hydrogen‐Bonded Quaterthiophene - Gebers, Jan; Özen, Bilal; Hartmann, Lucia; Schaer, Michel; Suàrez, Stéphane; Bugnon, Philippe; Scopelliti, Rosario; Steinrück, Hans-Georg; Konovalov, Oleg; Magerl, Andreas; Brinkmann, Martin; Petraglia, Riccardo; et al. (Chemistry – A European Journal)

Impact of Processing on Structural and Compositional Evolution in Mixed Metal Halide Perovskites during Film Formation - Abdelsamie, Maged; Xu, Junwei; Bruening, Karsten; Tassone, Christopher J.; Steinrück, Hans-Georg; Toney, Michael F. (Advanced Functional Materials)

Heterogeneous Behavior of Lithium Plating during Extreme Fast Charging - Tanim, Tanvir R.; Paul, Partha P.; Thampy, Vivek; Cao, Chuntian; Steinrück, Hans-Georg; Nelson Weker, Johanna; Toney, Michael F.; Dufek, Eric J.; Evans, Michael C.; Jansen, Andrew N.; Polzin, Bryant J.; Dunlop, Alison R.; et al. (Cell Reports Physical Science)

Advanced Characterization in Clean Water Technologies - Bone, Sharon E.; Steinrück, Hans-Georg; Toney, Michael F. (Joule)

Understanding additive controlled lithium morphology in lithium metal batteries - Kasse, Robert M.; Geise, Natalie R.; Ko, Jesse S.; Nelson Weker, Johanna; Steinrück, Hans-Georg; Toney, Michael F. (Journal of Materials Chemistry A)
Investigation of the mechanisms underlying control of electrodeposited lithium metal morphology using electrolyte additives in lithium metal batteries.

Time‐Resolved Structural Kinetics of an Organic Mixed Ionic–Electronic Conductor - Paulsen, Bryan D.; Wu, Ruiheng; Takacs, Christopher J.; Steinrück, Hans-Georg; Strzalka, Joseph; Zhang, Qingteng; Toney, Michael F.; Rivnay, Jonathan (Advanced Materials)

Interfacial Speciation Determines Interfacial Chemistry: X‐ray‐Induced Lithium Fluoride Formation from Water‐in‐salt Electrolytes on Solid Surfaces - Steinrück, Hans-Georg; Cao, Chuntian; Lukatskaya, Maria R.; Takacs, Christopher J.; Wan, Gang; Mackanic, David G.; Tsao, Yuchi; Zhao, Jingbo; Helms, Brett A.; Xu, Kang; Borodin, Oleg; Wishart, James F.; et al. (Angewandte Chemie International Edition)

Concentration and velocity profiles in a polymeric lithium-ion battery electrolyte - Steinrück, Hans-Georg; Takacs, Christopher J.; Kim, Hong-Keun; Mackanic, David G.; Holladay, Benjamin; Cao, Chuntian; Narayanan, Suresh; Dufresne, Eric M.; Chushkin, Yuriy; Ruta, Beatrice; Zontone, Federico; Will, Johannes; et al. (Energy & Environmental Science)
Direct measurements of concentration and velocity profiles in a polymeric lithium-ion battery electrolyte provide insights into the transference number.

Interface between Water–Solvent Mixtures and a Hydrophobic Surface - Prihoda, Annemarie; Will, Johannes; Duchstein, Patrick; Becit, Bahanur; Lossin, Felix; Schindler, Torben; Berlinghof, Marvin; Steinrück, Hans-Georg; Bertram, Florian; Zahn, Dirk; Unruh, Tobias (Langmuir)

Tortuosity Effects in Lithium-Metal Host Anodes - Chen, Hao; Pei, Allen; Wan, Jiayu; Lin, Dingchang; Vilá, Rafael; Wang, Hongxia; Mackanic, David; Steinrück, Hans-Georg; Huang, William; Li, Yuzhang; Yang, Ankun; Xie, Jin; et al. (Joule)

Toward quantifying capacity losses due to solid electrolyte interphase evolution in silicon thin film batteries - Steinrück, Hans-Georg; Cao, Chuntian; Veith, Gabriel M.; Toney, Michael F. (The Journal of Chemical Physics)

Effect of DNA Origami Nanostructures on hIAPP Aggregation - Hanke, Marcel; Gonzalez Orive, Alejandro; Grundmeier, Guido; Keller, Adrian (Nanomaterials)
The aggregation of human islet amyloid polypeptide (hIAPP) plays a major role in the pathogenesis of type 2 diabetes mellitus (T2DM), and numerous strategies for controlling hIAPP aggregation have been investigated so far. In particular, several organic and inorganic nanoparticles (NPs) have shown the potential to influence the aggregation of hIAPP and other amyloidogenic proteins and peptides. In addition to conventional NPs, DNA nanostructures are receiving more and more attention from the biomedical field. Therefore, in this work, we investigated the effects of two different DNA origami nanostructures on hIAPP aggregation. To this end, we employed in situ turbidity measurements and ex situ atomic force microscopy (AFM). The turbidity measurements revealed a retarding effect of the DNA nanostructures on hIAPP aggregation, while the AFM results showed the co-aggregation of hIAPP with the DNA origami nanostructures into hybrid peptide–DNA aggregates. We assume that this was caused by strong electrostatic interactions between the negatively charged DNA origami nanostructures and the positively charged peptide. Most intriguingly, the influence of the DNA origami nanostructures on hIAPP aggregation differed from that of genomic double-stranded DNA (dsDNA) and appeared to depend on DNA origami superstructure. DNA origami nanostructures may thus represent a novel route for modulating amyloid aggregation in vivo.

Protein-Assisted Room-Temperature Assembly of Rigid, Immobile Holliday Junctions and Hierarchical DNA Nanostructures - Ramakrishnan, Saminathan; Subramaniam, Sivaraman; Kielar, Charlotte; Grundmeier, Guido; Stewart, A. Francis; Keller, Adrian (Molecules)
Immobile Holliday junctions represent not only the most fundamental building block of structural DNA nanotechnology but are also of tremendous importance for the in vitro investigation of genetic recombination and epigenetics. Here, we present a detailed study on the room-temperature assembly of immobile Holliday junctions with the help of the single-strand annealing protein Redβ. Individual DNA single strands are initially coated with protein monomers and subsequently hybridized to form a rigid blunt-ended four-arm junction. We investigate the efficiency of this approach for different DNA/protein ratios, as well as for different DNA sequence lengths. Furthermore, we also evaluate the potential of Redβ to anneal sticky-end modified Holliday junctions into hierarchical assemblies. We demonstrate the Redβ-mediated annealing of Holliday junction dimers, multimers, and extended networks several microns in size. While these hybrid DNA–protein nanostructures may find applications in the crystallization of DNA–protein complexes, our work shows the great potential of Redβ to aid in the synthesis of functional DNA nanostructures under mild reaction conditions.

Self-assembly of highly ordered DNA origami lattices at solid-liquid interfaces by controlling cation binding and exchange - Xin, Yang; Martinez Rivadeneira, Salvador; Grundmeier, Guido; Castro, Mario; Keller, Adrian (Nano Research)
Abstract The surface-assisted hierarchical self-assembly of DNA origami lattices represents a versatile and straightforward method for the organization of functional nanoscale objects such as proteins and nanoparticles. Here, we demonstrate that controlling the binding and exchange of different monovalent and divalent cation species at the DNA-mica interface enables the self-assembly of highly ordered DNA origami lattices on mica surfaces. The development of lattice quality and order is quantified by a detailed topological analysis of high-speed atomic force microscopy (HS-AFM) images. We find that lattice formation and quality strongly depend on the monovalent cation species. Na + is more effective than Li + and K + in facilitating the assembly of high-quality DNA origami lattices, because it is replacing the divalent cations at their binding sites in the DNA backbone more efficiently. With regard to divalent cations, Ca 2+ can be displaced more easily from the backbone phosphates than Mg 2+ and is thus superior in guiding lattice assembly. By independently adjusting incubation time, DNA origami concentration, and cation species, we thus obtain a highly ordered DNA origami lattice with an unprecedented normalized correlation length of 8.2. Beyond the correlation length, we use computer vision algorithms to compute the time course of different topological observables that, overall, demonstrate that replacing MgCl 2 by CaCl 2 enables the synthesis of DNA origami lattices with drastically increased lattice order.

Quantitative Assessment of Tip Effects in Single‐Molecule High‐Speed Atomic Force Microscopy Using DNA Origami Substrates - Kielar, Charlotte; Zhu, Siqi; Grundmeier, Guido; Keller, Adrian (Angewandte Chemie International Edition)

Dynamics of lattice defects in mixed DNA origami monolayers - Xin, Yang; Ji, Xueyin; Grundmeier, Guido; Keller, Adrian (Nanoscale)
DNA origami lattice formation at solid–liquid interfaces is surprisingly resilient toward the incorporation of DNA origami impurities with different shapes.

Cryopreservation of DNA Origami Nanostructures - Xin, Yang; Kielar, Charlotte; Zhu, Siqi; Sikeler, Christoph; Xu, Xiaodan; Möser, Christin; Grundmeier, Guido; Liedl, Tim; Heuer‐Jungemann, Amelie; Smith, David M.; Keller, Adrian (Small)

Challenges and Perspectives of DNA Nanostructures in Biomedicine - Keller, Adrian; Linko, Veikko (Angewandte Chemie International Edition)

Amyloid aggregation at solid-liquid interfaces: Perspectives of studies using model surfaces - Keller, Adrian; Grundmeier, Guido (Applied Surface Science)

Arranging Small Molecules with Subnanometer Precision on DNA Origami Substrates for the Single‐Molecule Investigation of Protein–Ligand Interactions - Huang, Jingyuan; Suma, Antonio; Cui, Meiying; Grundmeier, Guido; Carnevale, Vincenzo; Zhang, Yixin; Kielar, Charlotte; Keller, Adrian (Small Structures)

Molecular adhesion science and engineering of nanostructured poly(acrylic acid)/metal oxide interfaces - Meinderink, Dennis
Das grundlegende Verständnis von makroskopischen Haftungsphänomenen beginnt bei der Analyse von molekularen Wechselwirkungen unter kontrollierten Bedingungen (Materialeigenschaften, chemische Oberflächenzusammensetzung, und weiteren Einflussfaktoren wie z.B. pH-Wert, Elektrolytzusammensetzung). In dieser Arbeit wurden die molekularen und makroskopischen Haftungseigenschaften von makromolekularer Poly(acrylsäure) (PAA) als potenzieller Haftungsvermittler auf Edelstahl und verschiedenen nanostrukturierten Zinkoxid (ZnO) Oberflächen untersucht, die mittels elektrochemischer und hydrothermalen Abscheidemethoden auf Edelstahl und feuerverzinktem Stahl (HDG) abgeschieden wurden. Molekulare Haftungsmechanismen zwischen PAA und ZnO basierend auf multi-koordinativen Bindungen in Abhängigkeit von der Oberflächenchemie und der Verweilzeit konnten mit der s.g. Einzelmolekülspektroskopie aufgeklärt werden. Die Ergebnisse aus weiteren makroskopischen Enthaftungsexperimenten und Rückseitenanalytik bei der Verwendung von verdünnten, wässrigen PAA-Lösungen zur Vorbehandlung von nanostrukturierten ZnO Filmen auf HDG Stahl untermauerten die starken Wechselwirkungen zwischen ZnO-PAA. Mittels Elektropolymerisation abgeschiedene PAA Filme zeigten eine signifikante Steigerung in den makroskopischen Haftungseigenschaften bei einem ausgewählten Model-Epoxid-Amin-Klebstoff auf Edelstahl. Die Kombination von ZnO Tetrapoden (ZnO TP) und PAA als hybridische, haftungsverbessernde Sprühbeschichtungen aus wässrigen Dispersionen auf Poly(propylen) Folien bestätigten, sowohl die chemischen, als auch mechanischen Haftungseigenschaften von nanostrukturierten ZnO/PAA Interphasen. Daher können PAA/Metalloxid-Grenzflächen die Tür in diversen technischen Ansätzen für innovative Anwendungen öffnen, wie z.B. in Sprühapplikationstechniken.

Spray pyrolysis of thin adhesion-promoting ZnO films on ZnMgAl coated steel - Grothe, R.; Knust, S.; Meinderink, Dennis; Voigt, M.; Orive, A. González; Grundmeier, Guido (Surface and Coatings Technology)

Kinetic studies of cathode degradation on PEM fuel cell short stack level undergoing freeze startups with different states of residual water and current draws - Liphardt, L.; Suematsu, K.; Grundmeier, Guido (International Journal of Hydrogen Energy)
Keywords: Energy Engineering and Power Technology; Condensed Matter Physics; Fuel Technology; Renewable Energy; Sustainability and the Environment

Single-Molecule Desorption Studies of Poly(acrylic acid) at Electrolyte/Oxide/TiAlN Interfaces - Schwiderek, Sabrina; Orive, Alejandro G.; Karimi Aghda, Soheil; Schneider, Jochen M.; de los Arcos de Pedro, Maria Teresa; Grundmeier, Guido (Langmuir)

Characterisation of micropores in plasma deposited SiO x films by means of positron annihilation lifetime spectroscopy - Hoppe, C; Mitschker, F; Butterling, M; Liedke, M O; de los Arcos de Pedro, Maria Teresa; Awakowicz, P; Wagner, A; Grundmeier, Guido (Journal of Physics D: Applied Physics)

Influence of dielectric barrier plasma treatment of ZnMgAl alloy‐coated steel on the adsorption of organophosphonic acid monolayers - Knust, Steffen; Kuhlmann, Andreas; Orive, Alejandro G.; de los Arcos de Pedro, Maria Teresa; Grundmeier, Guido (Surface and Interface Analysis)

Self-lubricating coatings via PDMS micro-gel dispersions - Ressel, Joerg; Seewald, Oliver; Bremser, Wolfgang; Reicher, Hans-Peter; Strube, Oliver I. (Progress in Organic Coatings)

Nano-architectural complexity of zinc oxide nanowall hollow microspheres and their structural properties - Engelkemeier, Katja; Lindner, Jörg; Bürger, Julius; Vaupel, Kathrin; Hartmann, Marc; Tiemann, Michael; Hoyer, Kay-Peter; Schaper, Mirko (Nanotechnology)
Zinc oxide (ZnO) hollow spheres with defined morphology and micro-/nanostructure are prepared by a hydrothermal synthesis approach. The materials possess fine-leaved structures at their particle surface (nanowall hollow micro spheres). Morphology control is achieved by citric acid used as an additive in variable relative quantities during the synthesis. The structure formation is studied by various time-dependent ex situ methods, such as scanning electron microscopy, x-ray diffraction, and Raman spectroscopy. The fine-leaved surface structure is characterized by high-resolution transmission electron microscopy techniques (HRTEM, STEM), using a high-angle annular dark field detector, as well as by differential phase contrast analysis. In-depth structural characterization of the nanowalls by drop-by-drop ex situ FE-SEM analysis provides insight into possible structure formation mechanisms. Further investigation addresses the thermal stability of the particle morphology and the enhancement of the surface-to-volume ratio by heat treatment (examined by N2 physisorption).

Scalable and energy-efficient synthesis of CoxP for overall water splitting in alkaline media by high energy ball milling - Xue, Hongyao; Zhang, Haiqin; Fricke, Sebastian; Lüther, Marco; Yang, Zijiang; Meng, Alan; Bremser, Wolfgang; Li, Zhenjiang (Sustainable Energy & Fuels)
Earth-abundant catalysts based on transition metal phosphides (TMPs) such as CoxP have recently gained a lot of attention in the field of electrocatalysis and are usually acquired by chemical synthesis.

Structural Origins of Light-Induced Phase Segregation in Organic-Inorganic Halide Perovskite Photovoltaic Materials - Beal, Rachel E.; Hagström, Nanna Zhou; Barrier, Julien; Gold-Parker, Aryeh; Prasanna, Rohit; Bush, Kevin A.; Passarello, Donata; Schelhas, Laura T.; Brüning, Karsten; Tassone, Christopher J.; Steinrück, Hans-Georg; McGehee, Michael D.; et al. (Matter)

Shedding X-ray Light on the Interfacial Electrochemistry of Silicon Anodes for Li-Ion Batteries - Cao, Chuntian; Shyam, Badri; Wang, Jiajun; Toney, Michael F.; Steinrück, Hans-Georg (Accounts of Chemical Research)

Morphology of Organic Semiconductors Electrically Doped from Solution Using Phosphomolybdic Acid - Huang, Tzu-Yen; Larrain, Felipe A.; Borca, Carlos H.; Fuentes-Hernandez, Canek; Yan, Hongping; Schneider, Sebastian Alexander; Chou, Wen-Fang; Rodriguez-Toro, Victor A.; Steinrück, Hans-Georg; Cao, Chuntian; Sherrill, C. David; Kippelen, Bernard; et al. (Chemistry of Materials)

Solid Electrolyte Interphase on Native Oxide-Terminated Silicon Anodes for Li-Ion Batteries - Cao, Chuntian; Abate, Iwnetim Iwnetu; Sivonxay, Eric; Shyam, Badri; Jia, Chunjing; Moritz, Brian; Devereaux, Thomas P.; Persson, Kristin A.; Steinrück, Hans-Georg; Toney, Michael F. (Joule)

Self-Assembly of Fibrinogen in Aqueous, Thrombin-Free Solutions of Variable Ionic Strengths - Hämisch, Benjamin; Büngeler, Anne; Kielar, Charlotte; Keller, Adrian; Strube, Oliver; Huber, Klaus (Langmuir)

Enhancing the stability of DNA origami nanostructures: staple strand redesign versus enzymatic ligation - Ramakrishnan, Saminathan; Schärfen, Leonard; Hunold, Kristin; Fricke, Sebastian; Grundmeier, Guido; Schlierf, Michael; Keller, Adrian; Krainer, Georg (Nanoscale)
Merging of bridging staples with adjacent oligonucleotide sequences leads to a moderate increase of DNA origami stability, while enzymatic ligation after assembly yields a reinforced nanostructure with superior stability at up to 37 °C and in the presence of 6 M urea.

Effect of Staple Age on DNA Origami Nanostructure Assembly and Stability - Kielar, Charlotte; Xin, Yang; Xu, Xiaodan; Zhu, Siqi; Gorin, Nelli; Grundmeier, Guido; Möser, Christin; Smith, David M.; Keller, Adrian (Molecules)
DNA origami nanostructures are widely employed in various areas of fundamental and applied research. Due to the tremendous success of the DNA origami technique in the academic field, considerable efforts currently aim at the translation of this technology from a laboratory setting to real-world applications, such as nanoelectronics, drug delivery, and biosensing. While many of these real-world applications rely on an intact DNA origami shape, they often also subject the DNA origami nanostructures to rather harsh and potentially damaging environmental and processing conditions. Furthermore, in the context of DNA origami mass production, the long-term storage of DNA origami nanostructures or their pre-assembled components also becomes an issue of high relevance, especially regarding the possible negative effects on DNA origami structural integrity. Thus, we investigated the effect of staple age on the self-assembly and stability of DNA origami nanostructures using atomic force microscopy. Different harsh processing conditions were simulated by applying different sample preparation protocols. Our results show that staple solutions may be stored at −20 °C for several years without impeding DNA origami self-assembly. Depending on DNA origami shape and superstructure, however, staple age may have negative effects on DNA origami stability under harsh treatment conditions. Mass spectrometry analysis of the aged staple mixtures revealed no signs of staple fragmentation. We, therefore, attribute the increased DNA origami sensitivity toward environmental conditions to an accumulation of damaged nucleobases, which undergo weaker base-pairing interactions and thus lead to reduced duplex stability.

Real-Time Observation of Superstructure-Dependent DNA Origami Digestion by DNase I Using High-Speed Atomic Force Microscopy. - Ramakrishnan, S; Shen, B; Kostiainen, MA; Grundmeier, Guido; Keller, Adrian; Linko, V (ChemBioChem)

DNA origami directed 3D nanoparticle superlattice via electrostatic assembly. - Julin, S; Korpi, A; Shen, B; Liljeström, V; Ikkala, O; Keller, Adrian; Linko, V; Kostiainen, MA (Nanoscale)

Effect of Terminal Modifications on the Adsorption and Assembly of hIAPP(20–29) - Hajiraissi, Roozbeh; Hanke, Marcel; Gonzalez Orive, Alejandro; Duderija, Belma; Hofmann, Ulrike; Zhang, Yixin; Grundmeier, Guido; Keller, Adrian (ACS Omega)

Spray coating of poly(acrylic acid)/ZnO tetrapod adhesion promoting nanocomposite films for polymer laminates - Meinderink, Dennis; Nolkemper, Karlo J.R.; Bürger, Julius; Orive, Alejandro G.; Lindner, Jörg K.N.; Grundmeier, Guido (Surface and Coatings Technology)

Low-Temperature Plasma-Enhanced Atomic Layer Deposition of Tin(IV) Oxide from a Functionalized Alkyl Precursor: Fabrication and Evaluation of SnO2-Based Thin-Film Transistor Devices - Mai, Lukas; Zanders, David; Subaşı, Ersoy; Ciftyurek, Engin; Hoppe, Christian; Rogalla, Detlef; Gilbert, Wolfram; de los Arcos de Pedro, Maria Teresa; Schierbaum, Klaus; Grundmeier, Guido; Bock, Claudia; Devi, Anjana (ACS Applied Materials & Interfaces)

Potential Precursor Alternatives to the Pyrophoric Trimethylaluminium for the Atomic Layer Deposition of Aluminium Oxide - Mai, Lukas; Boysen, Nils; Zanders, David; de los Arcos de Pedro, Maria Teresa; Mitschker, Felix; Mallick, Bert; Grundmeier, Guido; Awakowicz, Peter; Devi, Anjana (Chemistry – A European Journal)